Monitoring Vegetative Stages of Spring Wheat (Triticum Aestivum L) with Sentinel-1 and Sentiel-2 Imagery in Bornuur soum, Tuv province, Mongolia - Lkhagvadulam, Sanjaatjamts; Badamgarav, Gansukh; Bayartungalag, Batsaikhan; Altangerel, Dursahinhan Tsogtsaikhan; Odgerel, Bold (Mongolian Geoscientist, 2025)
Spring wheat (Triticum aestivum Linnaeus, 1753) is critical for global food security, sustaining over 20% of the world’s population. In Mongolia, it is the primary staple crop, though production is affected by climatic and market fluctuations. This study, conducted at the “Nart” Research Center of the Mongolian University of Life Sciences in Bornuur soum, Tuv province, examined growth dynamics of the Darkhan-144 wheat variety using Sentinel-1 and Sentinel-2 satellite data. The crop, sown between May 21–25, 2020, achieved uniform germination within 15–20 days. Key phenophases included germination to main pricking (10 days), heading (15 days), flowering to milky seed stage (15 days), and milky to hybrid tuber (10 days), totaling a growth cycle of 85-90 days. The Normalized Difference Vegetation Index rose from ( 0.18) in early May to 0.80 by July and September. Normalized Difference Vegetation Index showed strong correlation with the Normalized Difference Water Index for wet biomass (R²=0.67) and dry biomass (R²=0.62). Sentinel-2 reflectance ranged from 0.05-0.40 in May and July, and 0.25-0.45 in June. Field spectrometer values increased from 0.35 in July to 0.60 nm in August, before declining to 0.30 nm in September. These findings reveal a strong correlation between vegetation water indices and wheat growth parameters, highlighting the potential of satellite-based spatiotemporal analysis to inform and enhance local policymaking in agricultural production and management. This study supports the integration of remote sensing into Mongolia’s crop monitoring strategies.